Both caffeine and Capsicum annuum fruit powder lower blood glucose levels and increase brown adipose tissue temperature in healthy adult males - Van Schaik, Lachlan; Kettle, Christine; Green, Rod; Wundersitz, Daniel; Gordon, Brett; Irving, Helen R.; Rathner, Joseph A. (Frontiers in Physiology, 2022)
Using a combination of respiratory gas exchange, infrared thermography, and blood glucose (BGL) analysis, we have investigated the impact of Capsicum annuum (C. annuum) fruit powder (475mg) or caffeine (100mg) on metabolic activity in a placebo controlled (lactose, 100mg) double-blinded three-way cross-over-design experiment. Metabolic measurements were made on day 1 and day 7 of supplementation in 8 adult male participants (22.2±2 years of age, BMI 23±2 kg/m2, x̅±SD). Participants arrived fasted overnight and were fed a high carbohydrate meal (90g glucose), raising BGL from fasting baseline (4.4±0.3mmol/L) to peak BGL (8.5±0.3mmol/L) 45 minutes after the meal. Participants consumed the supplement 45 minutes after the meal, and both caffeine and C. annuum fruit powder restored BGL (F (8,178) = 2.2, p= 0.02) to near fasting levels within 15 minutes of supplementation compared to placebo (120 minutes). In parallel both supplements increased energy expenditure (F (2, 21) = 175.6, p <0.001) over the 120-minute test period (caffeine= 50.74 ± 2 kcal/kg/min, C. annuum fruit=50.95 ± 1 kcal/kg/min, placebo=29.34 ± 1 kcal/kg/min). No statistically significant difference in mean arterial pressure or heart rate was observed due to supplementation nor was any statistical difference seen between day 1 and day 7 of intervention. This is important for implementing dietary ingredients as potential metabolism increasing supplements. Together the results imply that through dietary supplements such as caffeine and C. annuum, mechanisms for increasing metabolism can be potentially targeted to improve metabolic homeostasis in people.